2017
DOI: 10.3389/fpls.2017.01806
|View full text |Cite
|
Sign up to set email alerts
|

Host–Multi-Pathogen Warfare: Pathogen Interactions in Co-infected Plants

Abstract: Studies of plant–pathogen interactions have historically focused on simple models of infection involving single host-single disease systems. However, plant infections often involve multiple species and/or genotypes and exhibit complexities not captured in single host-single disease systems. Here, we review recent insights into co-infection systems focusing on the dynamics of host-multi-pathogen interactions and the implications for host susceptibility/resistance. In co-infection systems, pathogen interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(173 citation statements)
references
References 111 publications
(136 reference statements)
3
164
0
6
Order By: Relevance
“…and P. pinodella , explain site‐specific resistance rankings and detected QTL. Abdullah et al () concluded that resistance capacities of pea cultivars against single pathogens, especially when determined under gnotobiotic conditions, have limited transferability to complex field conditions. To overcome such limitations, it is necessary to consider complex plant–microbe interactions and develop screening systems that account for multiple interactions among pathogens, beneficial microbes, and the host plant genotype.…”
Section: Complex Interactions Between Grain Legumes and Their Root‐asmentioning
confidence: 99%
See 1 more Smart Citation
“…and P. pinodella , explain site‐specific resistance rankings and detected QTL. Abdullah et al () concluded that resistance capacities of pea cultivars against single pathogens, especially when determined under gnotobiotic conditions, have limited transferability to complex field conditions. To overcome such limitations, it is necessary to consider complex plant–microbe interactions and develop screening systems that account for multiple interactions among pathogens, beneficial microbes, and the host plant genotype.…”
Section: Complex Interactions Between Grain Legumes and Their Root‐asmentioning
confidence: 99%
“…and P. pinodella, explain site-specific resistance rankings and detected QTL. Abdullah et al (2017) concluded that resistance capacities of pea cultivars against single pathogens, especially when determined under gnotobiotic conditions, have limited transferability to complex field conditions.…”
Section: The Dilemma With Pathogen Complexesmentioning
confidence: 99%
“…However, plant infections often involve multiple species and/or genotypes and exhibit complexities not captured in single host single disease systems. Here, pathogen interactions include: (i) Competition, in which competing pathogens develop physical barriers or utilize toxins to exclude competitors from resourcedense niches; (ii) Cooperation, whereby pathogens beneficially interact, by providing mutual biochemical signals essential for pathogenesis, or through functional complementation via the exchange of resources necessary for survival; (iii) Coexistence, whereby pathogens can stably coexist through niche specialization [31]. Furthermore, hosts are also able to, actively or passively; modulate niche competition through defense responses that target at least one pathogen [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Plants were sampled for concentration of salicylic acid phytohormone at 4.5 h, 24 h, and 4 weeks after viral inoculation during two experimental replicates. Salicylic acid (SA) is known to be involved in plant responses to biotrophic pathogens such as viruses (Abdullah et al 2017). At the same time, exogenous SA has been shown to inhibit the initiation of rhizobia nodules (Sato et al 2002, Mabood andSmith 2007).…”
Section: Experimental Designmentioning
confidence: 99%